Empowerment in women with the condition of vulnerability of human settlements from the Chorrillos district - Lizarzaburu Otiniano, Laura Isabela (2018)
This investigation has been made considering a quantitative focus with a non-experimental design and a transverse section in a descriptive level which statistical analysis is univariate. The main objective is to understand the level of empowerment of women in a state of vulnerability that lives in the shanty towns in the district of Chorrillos. These may or may not participant in social programs. The tool that was used to make the evaluation on the women is the Instrumento para la Medición del Empoderamiento de Mujeres (known in Spanish as IMEM). It was designed by Universidad Juárez Autónoma of Tabasco in Mexico (Hernandez and García 2008). The sample was formed by 87 women with similar characteristics, 40 of them were currently participating in a social program and the other 47 were not. The results showed that 67.5% of the women that participate in a social program possess a higher level of empowerment in comparison to 4.30% of women who do not participate in a social program.